2017
DOI: 10.1200/po.17.00146
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a Clinically Applicable Mutational Burden Threshold as a Potential Biomarker of Response to Immune Checkpoint Therapy in Solid Tumors

Abstract: Purpose An association between mutational burden and response to immune checkpoint therapy has been documented in several cancer types. The potential for such a mutational burden threshold to predict response to immune checkpoint therapy was evaluated in several clinical datasets, where mutational burden was measured either by whole-exome sequencing (WXS) or using commercially available sequencing panels. Methods WXS and RNA-seq data of 33 solid cancer types from TCGA were analyzed to determine whether a rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 43 publications
1
54
0
Order By: Relevance
“…Besides the accuracy of panel-based TMB quantification, it is critical to assess its capability to discriminate between immunotherapy responders and nonresponders, as previously observed for WES-based TMB. Several exploratory analyses demonstrated that panelbased TMB, as simulated in silico by downsampling a WES dataset to only include genes targeted by the Foun-dationOne gene panel, associates with immunotherapy response [8,26] or with signatures of immune checkpoint activation [38]. Comparable results were observed in similar in silico analyses for other gene panels, such as the Trusight170 [39,40] or MSK-IMPACT [26] (Additional file 4: Table S4).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Besides the accuracy of panel-based TMB quantification, it is critical to assess its capability to discriminate between immunotherapy responders and nonresponders, as previously observed for WES-based TMB. Several exploratory analyses demonstrated that panelbased TMB, as simulated in silico by downsampling a WES dataset to only include genes targeted by the Foun-dationOne gene panel, associates with immunotherapy response [8,26] or with signatures of immune checkpoint activation [38]. Comparable results were observed in similar in silico analyses for other gene panels, such as the Trusight170 [39,40] or MSK-IMPACT [26] (Additional file 4: Table S4).…”
mentioning
confidence: 86%
“…Moreover, the adopted cutoffs sometimes differ across different studies on the same gene panel (Table 1). Up to now, the TMB cutoff of 10 mutations per Mb, measured by the FoundationOne gene panel and found to best discriminate between responders and non-responders to immunotherapy in NSCLC patients, is the only one which has been validated in a separate further study [28,50,51]; this cutoff was also observed, but not yet validated, in melanoma [38] and in metastatic urothelial carcinoma [15] (Table 1). Interestingly, these cancer types present a TMB distribution similar to that of NSCLC [52].…”
Section: Need For Standardization Of Tmb Quantification and Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it is not clear what the right TMB threshold should be to optimally identify potential responders, or www.annualreviews.org • Biomarkers for Response to ICB 335 if TMB functions as a predictor of response only in some cancer classes. A pan-cancer analysis of TCGA (The Cancer Genome Atlas) data has demonstrated that an optimal TMB threshold that identifies tumors with evidence of lymphocytic infiltration and immune checkpoint gene expression may only be present in some cancer classes (Panda et al 2017). Moreover, different cancer types may have different TMB cutoffs to optimally predict response (Panda et al 2017, Samstein et al 2019.…”
Section: Figurementioning
confidence: 99%
“…Questions remain however, as TMB is influenced by many biological and technical factors such as ploidy, tumor heterogeneity and clonality (ASCO SITC 2019, Abstract 27), sample tumor cell content, sequencing depth, and variant filtering. Which cutoff to use for stratifying patients into TMB groups is also still emerging [109,110], and specifically in RNA-seq has to our knowledge not been addressed. Due to this, and to account for different expression profiles per tumor, we decided to use the median amount of non-synonymous mutations per MB of transcriptome across the cohort (0.08 mutations) to stratify patients into TMB high and low groups and use it to study OS in different conventional treatment and biomarker subgroups.…”
Section: Tumor Mutational Burdenmentioning
confidence: 99%